Functional Interhemispheric Asymmetry and Neurocognitive Development in Children and Teenagers - N.A. Khokhlov (Клиническая и специальная психология)
Many neuropsychologists believe that left-handed individuals are more likely to experience developmental disorders. In addition, non-coinciding lateralization of analyzers (cross-laterality) is also considered as a possible factor in dysontogenesis. However, in recent years it has been demonstrated that functional interhemispheric asymmetry (FIA) has minimal impact on intelligence and quality of life. This study aims to measure the contribution of manual and visual asymmetries to the overall level of neurocognitive development (ND) in children and adolescents. A total of 922 individuals were studied, including 594 boys and 328 girls aged 4–17 years, who underwent neuropsychological diagnostics. The scale of general level of development from the psychometric battery “Multifactorial Investigation of Neuropsychological Development” was used. The measurement of seven FIA indicators was carried out by observing subjects and assessing the performance on five techniques for lateral signs. No significant influence on ND was found for FIA and cross-lateralization. In some age groups, lateral signs were associated with ND, but this association was not stable. Additionally, it was shown that the results of techniques for lateral signs are inconsistent with each other.